Extraction of Scandium and Removal of Iron from Bauxite Residue using Hydrochloric Acid Solution with/without Addition of EDTA - Sitorus, Berlian; Reva, Mincen; Syahbanu, Intan (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Scandium (Sc) is a strategic metal for its increasing demand for advanced materials applications. As a by-product of alumina production, bauxite residues possess a potential source of Sc. However, its high iron content hinders the Sc extraction efficiency. This study investigated the feasibility of Sc extraction from bauxite residue using hydrochloric acid (HCl) leaching process, with and without the addition of ethylenediaminetetraacetic acid (EDTA) as a chelating agent. Bauxite residue samples were characterized for their elemental composition using the X-ray fluorescence (XRF) spectroscopy. Subsequently, leaching experiments were conducted using 6M and 9M HCl solutions. The effect of EDTA on Sc extraction yield and iron dissolution was assessed. The XRF analysis revealed a significant iron content in the bauxite residue, confirming the need for effective iron removal. Hydrochloric acid was found to be effective in leaching iron (Fe) from bauxite residue, as confirmed by the high Fe content in the leachate, and a higher HCl concentration led to a higher Sc2O3 concentration in the residue. Although the addition of EDTA was effective in chelating iron, it also reduced Sc extraction efficiency. The leaching results suggested the use of 9M HCl without the addition of EDTA as the best leaching solution for Sc extraction, yielding a higher Sc recovery compared to extractions using 6M HCl and EDTA. These findings contribute to the understanding of Sc extraction from bauxite residue and provide valuable insights for developing efficient and sustainable recovery processes.